The experienced "sense" of a virtual community: characteristics and processes - Blanchard, Anita L.; Markus, M. Lynne (ACM SIGMIS Database: the DATABASE for Advances in Information Systems, 2004)
E-commerce strategists advise companies to create virtual communities for their customers. But what does this involve? Research on face-to-face communities identifies the concept of "sense of community:" a characteristic of successful communities distinguished by members' helping behaviors and members' emotional attachment to the community and other members. Does a sense of virtual community exist in online settings, and what does it consist of? Answering these questions is key, if we are to provide guidance to businesses attempting to create virtual communities.The paper explores the concept of sense of virtual community in a newsgroup we call Multiple Sports Newsgroup (MSN). We first demonstrate that MSN does indeed have a sense of virtual community, but that the dimensions of the sense of community in MSN differ somewhat from those reported for physical communities. The nature of these differences is plausibly related to the differences between electronic and face-to-face communication. We next describe the behavioral processes that contribute to the sense of virtual community at MSN-exchanging support, creating identities and making identifications, and the production of trust. Again, these processes are similar to those found in non-virtual communities, but they are related to the challenges of electronic communication. Lastly, we consider the question of how sense of community may come about and discuss the implications for electronic business.